Competitiveness and Export Similarity of Indonesian Horticulture in The Asean-Asean+3 - Nur Chasanah; Jangkung Handoyo Mulyo; Dwidjono Hadi Darwanto (Agro Ekonomi, 2017)
In the framework of ASEAN+3 integration, Indonesian horticultural trade is facing a dilemmatic position. Being in the middle of a fi erce competition with benchmark countries, it is important that Indonesia gain the highest profi t from its integration strategy. Evaluation is n of needed to investigate Indonesian’s position in ASEAN +3 horticultural markets and the sustainability of specifi c trading prospect on each member country. Therefore, this study aims to investigate competitiveness and similarity of Indonesian horticultural export structure in intra-ASEAN+3. Revealed Comparative Advantage (RCA) analysis shows that Indonesian horticulture does not have aggregate competitiveness in ASEAN+3 market. The average of Indonesian RCA decreased from 1,64 in ASEAN level during 1999-2014 to 0,45 in ASEAN+3 level. In addition, based on Export Similarity Index (ESI) analysis, Indonesia has the highest and the most consistent similarity of horticultural export structure with Singapore, both in ASEAN and ASEAN+3 level. Meanwhile, Thailand has the highest level of export structure similarity in ASEAN with ESI index of 93,77. Integration of ASEAN+3 has led to an alteration in trading scheme in which ESI with each member country generally decrease. The highest level of export structure similarity occurs with Singapore with ESI index of 85,95. Overall, the trade of horticultural commodity in the framework of ASEAN+3 integration is dominated by export structure similarity which may lead to a competition between the members of ASEAN+3.